ANALISIS GAYA BAHASA ALITERASI DALAM 10 PUISI KARYA MUSTOFA BISRI - Setyaningsih, Arinda Oktariski (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Each literary work has its own characteristics and uniqueness so that it becomes its own main attraction, one of which is poetry. The purpose of this study was to analyze the alliteration of figurative language found in 10 poems by Mustofa Bisri. The method used in this study, namely using a qualitative descriptive method. The data sources used came from 10 poems by Mustofa Bisri, namely (1) My country, (2) When Are You Busy When You Have Time, (3) My Teacher, (4) My Wife, (5) Important People, (6) Choices, ( 7) To the Poets, (8) Love Poems, (9) So What Else, and (10) Suwuk Manikcemar. While the data studied is the style of language alliteration. Data collection was carried out by random sampling using techniques of reading, noting, and classifying figurative language alliteration. These data are then presented in the form of data tables and pie charts to make it easier to present the data in detail. To test the validity of the data, researchers used theoretical triangulation by checking the correctness of the data.